Insulin sensitivity, islet cell function, and incretin axis in pregnant women with and without gestational diabetes mellitus - Niya Narayanan; Jayaprakash Sahoo; Sadishkumar Kamalanathan; Haritha Sagili; Bobby Zachariah; Dukhabandhu Naik; Ayan Roy; Chandhana Merugu (Indian Journal of Endocrinology and Metabolism, 2024)
Introduction: The aim of this study was to compare insulin sensitivity, islet cell function, and incretin axes in pregnant subjects with GDM and normal healthy controls. Methods: Pregnant women at 24 to 28 weeks of gestation were subjected to a 75 g oral glucose tolerance test (OGTT). Samples for glucose, insulin, glucagon, glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) were collected at 0, 30, 60, and 120 min during the OGTT. The Matsuda index (MI) and insulin secretion and sensitivity index-2 (ISSI-2) were assessed. The glucagon suppression index (GSI) was calculated along with the area under the curve (AUC) for glucose, insulin, glucagon, GLP-1, and GIP. Results: A total of 48 pregnant women (25 GDM and 23 controls) were finally analysed. The MI and ISSI-2 were low in the GDM group [4.31 vs. 5.42; P = 0.04], [1.99 vs. 3.18, P ≤ 0.01] respectively). Total AUCglucagon was higher in the GDM group (7411.7 vs. 6320.1, P = 0.02). GSI30 was significantly lower in the GDM group (-62.6 vs. -24.7, P = 0.03). Fasting GLP-1 levels were low in GDM women (17.3 vs. 22.2, P = 0.04). The total AUCGLP-1 positively correlated with total GSI in the GDM group. Conclusion: Asian-Indian GDM women have high insulin insensitivity, islet cell dysfunction, and low fasting GLP-1. Incretin axis dysfunction plays a potential role in their islet cell dysfunction.